DATABASE-BASED GUI SYSTEM TO INCREASE THE EFFECTIVENESS OF STUDENT DATA MANAGEMENT IN THE FKIP UHAMKA DORMITORY - AMURU, ISMAT; Dzikrillah, Akhmad Rizal (Informatika, Universitas Jenderal Soedirman, 2024)
Data management in the digital era is crucial in various institutions. One of these institutions is the dormitory or student residence, where it's important to track the progress achieved by the residents. However, data management at the FKIP UHAMKA Dormitory still faces several challenges, particularly regarding the loss of previous evaluation data, which is essential for the management. Data loss is a significant issue in the data management process for the relevant institution. Hence, there is a need for innovation in designing a database system that is user-friendly for data management in the digital era. This research aims to develop a GUI-based database system to efficiently manage student data at the FKIP UHAMKA Dormitory. The research adopts the waterfall development method, which involves stages such as requirements analysis, design, coding, and testing. Data is obtained through observation, interviews, and literature studies. The results of the research indicate that the GUI application based on the Dormitory FKIP UHAMKA Database has a good level of usability, with a System Usability Scale (SUS) score of 73.654. This suggests that users find the application easy to use and efficient in meeting their needs related to dormitory management. In addition to the SUS evaluation, this research stands out for developing a more comprehensive GUI system with significant additional features.